Micropropagation of ash (Fraxinus excelsior L.) - Abbott, Jane I. E. (Trinity College (Dublin, Ireland). Department of Botany, 2005)
Ash (Fraxinus excelsior L.) is a native hardwood species in Ireland used as a fast growing tree that is well adapted to agricultural sites. It produces wood valued for its toughness and elasticity. A key objective for Its agronomic improvennent is to develop means to vegetatively propagate selected mature trees. Seed progeny is heterogeneous, and requires a long period of growing out time before plus trees can be identified. By identifying mature plus trees (selected trees) and vegetatively propagating them it is possible to make testing more efficient and to gain valuable time in tree breeding programs. However, in the mature phase, characterised by flowering and a loss of organogenic competence, most forest species are recalcitrant to standard vegetative propagation methods. In vitro culturing methods offer a way around this obstacle and have been assessed in this thesis. Mature ash trees, displaying characteristics desirable for forestry, were phenotypically selected by Collite from sources around Ireland and conserved as grafted plants in Kilmacurra, Co. Wicklow and at Teagasc Kinsealy Research Centre, Co. Dublin. These plants were used in experiments to improve the micropropagation protocols for ash and to develop new methods. The thesis also studied the polyamine production of ash shoots in vitro as stress indicators, analysed the genetic fidelity of the vegetative propagules and assessed the genetic diversity of a sample of the selected trees (the breeding population).
Keywords: Botany, Ph.D.; Ph.D. Trinity College Dublin